Facial and Periorbital Cellulitis due to Skin Peeling with Jet Stream by an Unauthorized Person - Asli Feride Kaptanoglu; Didem Mullaaziz; Kaya Suer (Case Reports in Dermatological Medicine)
Technologies and devices for cosmetic procedures are developing with each passing day. However, increased and unauthorized use of such emerging technologies may also lead to increases in unexpected results and complications as well. Here, we report a case of facial cellulitis after a “beauty parlor” session of skin cleaning with jet stream peeling device in 19-year old female patient for the first time. Complications due to improper and unauthorized use of jet stream peeling devices may also cause doubts about the safety and impair the reputation of the technology as well. In order to avoid irreversible complications, local authorities should follow the technology and update the regulations where the dermatologists should take an active role.